ChemInform Abstract: Asymmetric Michael Addition of N‐tert‐Butanesulfinyl Imidate with α, β‐Unsaturated Diesters: Scope and Application to the Synthesis of Indanone Derivatives. Issue 34 (1st August 2013) - Wang, Jinfang; Zhou, Yu; Zhang, Lei; Li, Zeng; Chen, Xianjie; Liu, Hong
Abstract The diastereoselective Michael addition of N‐tert‐butanesulfinyl imidate (I) to diethyl arylidenemalonates (II) is tolerant toward arylidenemalonates containing alicyclic, aryl, and heterocyclic groups.